ANALISIS FATWA DSN-MUI NO.40/DSN-MUI/X/2003 TENTANG PASAR MODAL DAN PEDOMAN UMUM PENERAPAN PRINSIP SYARIAN DI BIDANG PASAR MODAL - Afiyah, Ulfah Nur; Mahbub, Moch (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2019)
ABSTRACTThe analysis aims to know the background of the emergence of DSN-MUI Fatwa No.40/DSN-MUI/X/2003, the term application of sharia principles in fatwa as well as its comparation with POJK No.15 No.15/POJK.04/2015 on the Application of Sharia Principles in Capital Markets. The method used in this analysis takes the form of a juridical-normative method that is, by way of approaching the problem studied with the normative nature of the law that is to base oneself on norms and rules sourced on the terms of fatwa and POJK. The results of the study showed that the birth background of fatwa was because Muslims at the time needed guidelines in the implementation of capital markets that were in accordance with sharia principles. The use of the term sharia principle in capital markets because the general principle applied in capital markets is already aligned with the sharia principle and patterns used in Indonesia in the pattern of integration (integration). POJK is a result of fatwa legitimacy. The substance is both continuous, only that in POJK is mentioned regarding sanctions indicating the implementation of a more binding and legally-powered POJK.